Customer Loyalty is Affected by Service Quality, Product Quality, and Sales Promotion on Publishing Pareto Customers Erlangga Pekanbaru - Arianto, Hangga; Pradiani, Theresia; Maskan, Mohammad (Journal of Social Research, 2023)
Customer loyalty is an essential factor in business success. In the publishing industry, such as Pareto Publisher Erlangga, creating customer loyalty is crucial for maintaining a competitive market share. Therefore, this research aims to analyze the relationship between service quality, product quality, sales promotion, and customer loyalty among Publisher Erlangga's Pareto customers in Pekanbaru. This study adopts a quantitative approach by collecting data from 92 respondents who are customers of Pareto Publisher Erlangga in Pekanbaru. The research instrument used is a questionnaire consisting of questions about customer perceptions of service quality, product quality, sales promotion, and loyalty to Erlangga Publisher. The results of data analysis using the multiple linear regression method indicate that service quality, product quality, and sales promotion have a significant positive influence on customer loyalty. This means that the higher the customers' perception of service quality, product quality, and sales promotion, the higher their level of loyalty to Erlangga Publisher. These findings have important implications for Pareto Publisher Erlangga in Pekanbaru to enhance customer loyalty. They should focus on improving service quality, such as responsiveness to customer inquiries, speed of service, and ease of communication. Additionally, they should ensure that the products they offer are of high quality and meet customer expectations. Moreover, effective sales promotion strategies should also be implemented to build awareness and interest among customers. Pareto Publisher Erlangga in Pekanbaru can develop more effective strategies to maintain and increase their market share. This research can serve as a reference for the publishing industry and other businesses in understanding the importance of service quality, product quality, and sales promotion in fostering customer loyalty.